Surprising Taxonomies: A Book Review of Lauren Berlant and Kathleen Stewart’s The Hundreds - Kitchin, Adrienne (Journal of the Canadian Association for Curriculum Studies, 2023)
In this book review, the form and function of what the writing is doing in Lauren Berlant and Kathleen Stewart’s The Hundreds is one of the many points of focus. Following the lines of posthuman, new materialist, and affect theories, the poems (what the authors refer to as makings) offer a fresh and lively engagement with academic scholarship. This is a scholarship interwoven with creativity presenting an elsewhere of form for the merging of academic and creative thought. Berlant and Stewart use engaging ideas to offer their book as an encounter and allow for interactive opportunities for their readers. While this is a concise book at 173 pages, it has no shortage of depth and creativity, concepts that the reviewer explores.